MODERASI BERAGAMA RAMAH BUDAYA (I’TIBAR AL-‘URF) MENCARI KESEIMBANGAN ANTARA KEAGAMAAN DAN BUDAYA NYADRAN YANG ADA DI PEKALONGAN - Ishmatuddiana Ishmatuddiana; Deswita Putri Widodo; Natasya Hildayatu Naila; Achmad Tubagus Surur (JOURNAL SAINS STUDENT RESEARCH, 2025)
Religious moderation is behavior that lies between religious practice and believing in and respecting different religious practices and beliefs. One of the traditional ceremonies of the Pekalongan people which contains the value of religious moderation is the Nyadran tradition. The purpose of this study is to find out how the Nyadran tradition procession is carried out, what the meaning and philosophical function behind the Nyadran tradition is, and how to implement religious values in the Nyadran tradition in Pekalongan. In this research, the author used qualitative methods and literature review methods. Qualitative methods for data collection were carried out through observation and interviews with sources. The method used in this research can be divided into three stages: (1) collecting the data needed for the study, (2) conducting interviews with resource persons in the field, and (3) recording data from the interview results. The data study method itself is the method used by the author by interviewing the village community in Pekalongan directly. The results of this research show that religious moderation is indeed expressed in the Nyadran Pekalongan tradition.